2008
DOI: 10.2478/v10045-008-0046-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitin and Abamectin on Meloidogyne Incognita Infesting Rapeseed

Abstract: Abstract:The tested rates of chitin (2, 4 and 8 g/m 2 ) significantly (p ≤ 0.05 and 0.01) reduced the number of galls, egg masses, females and the second stage juveniles (J 2 ) in oilseed rape cvAD201 under field conditions. The plant growth parameters as length and weight of shoots increased at all rates of chitin compared to the untreated check. When using abamectin at the concentrations of 500, 1000and 1500 ppm, it significantly (p ≤ 0.05) reduced the above listed nematode criteria and enhanced the plant gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 10 publications
(10 reference statements)
0
9
0
Order By: Relevance
“…In addition, Kalaiarasan et al (2006) showed that soil treatment with chitin promoted the plant growth and increased the yield of groundnut, reduced nematode population, and enhanced soil microbial activity up to 55%. Recently, Korayem et al (2008) stated that chitin applied at rates of 2, 4, and 8 g/m² significantly (p≤0.05) reduced M. incognita reproduction and increased plant growth parameters of rapeseed. A significant decrease in both M. incognita eggs and J 2 was noticed when chitin rates were increased at 100 and 200 g/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kalaiarasan et al (2006) showed that soil treatment with chitin promoted the plant growth and increased the yield of groundnut, reduced nematode population, and enhanced soil microbial activity up to 55%. Recently, Korayem et al (2008) stated that chitin applied at rates of 2, 4, and 8 g/m² significantly (p≤0.05) reduced M. incognita reproduction and increased plant growth parameters of rapeseed. A significant decrease in both M. incognita eggs and J 2 was noticed when chitin rates were increased at 100 and 200 g/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…There has been an enhancement in the exploitation of bio-control methods for integrated management of plant parasitic nematodes using ubiquitous antagonistic organisms. Such methods are meant to minimize environmental pollution from chemical control and to keep the root-knot nematode management processes more economical for cowpea farmers in Nigeria (Cabamillas and Baker 1989;Thompson 1998;Maareg and Badr 2000;Korayem et al 2008;Yousef et al 2008;Oclarit et al 2009). Beside these, arbuscular mycorrhizal fungi (AMF) are ubiquitous in the soil and are commonly symbiotic with the root systems of many crops supporting shoot growth and phosphorus nutrition in cowpea (Bethlenfalvay and Liderman 1992;Barea and Jefferies 1995).…”
Section: Introductionmentioning
confidence: 99%
“…When 0.075 g (ST 1 ), 0.150 g (ST 2 ), 0.300 g (ST 3 ) and 0.600 g (ST 4 ) of abamectin were used for seed treatment in combination with 0.088 g of thiabendazole and 0.192 g of thiamethoxam, a reduction of 64%, 49%, 33% and 30%, respectively, was seen for the number of galls per 10 g roots (Figure 4). Korayem et al (2008) reported that application of abamectin at the tested concentrations significantly reduced most nematode parameters while simultaneously enhancing plant growth parameters. A study by Khalil (2013) In a study conducted by Faske and Starr (2007), the authors noted that abamectin is capable of protecting roots from RKN-mediated galling only for 5 cm along the growing root and further beyond, abamectin cannot protect the growing root.…”
Section: Effect Of Chemical Treatment On Reduction Of Root-knot Nematmentioning
confidence: 94%